Comparison of the Ventricle Muscle Proteome between Patients with Rheumatic Heart Disease and Controls with Mitral Valve Prolapse: HSP 60 May Be a Specific Protein in RHD. (12th March 2014) - Zheng, Dawei; Xu, Limin; Sun, Lebo; Feng, Qiang; Wang, Zishan; Shao, Guofeng; Ni, Yiming
Abstract : Objective . Rheumatic heart disease (RHD) is a serious autoimmune heart disease. The present study was aimed at identifying the differentially expressed proteins between patients with RHD and controls with mitral valve prolapse. Methods . Nine patients with RHD and nine controls with mitral valve prolapsed were enrolled for this study. Two-dimensional difference in-gel electrophoresis (2D-DIGE) and matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) were performed. Results . A total of 39 protein spots with differential expressions were identified between the two groups (P < 0.05, Average Ratio > 1.2 or Average Ratio < −1.2) and four upregulated proteins (including heat shock protein 60 (HSP 60), desmin, PDZ and LIM domain protein 1, and proteasome subunit alpha type-1) and three downregulated proteins (including tropomyosin alpha-1 chain, malate dehydrogenase, and chaperone activity of bc1 complex homolog) were determined. Conclusion . These seven proteins, especially HSP 60, may serve as potential biomarkers for the diagnosis of RHD and provide evidence to explain the mechanisms of this complex disease in the future.